Role of Cadre in Improving Knowledge and Attitude of Chronic Energy Deficiency on Teenagers in Mali-Mali Village, Banjar Regency, South Kalimantan, Indonesia - Noor, Meitria Syahadatina; Sari, Ayu Riana; Agustriyanto, R. Akbar; Norwinardi, Rezeki; Agustina, Diah; Rahmaniah, Erma; Safitri, Erwinda; Amalia, Gusti Firdha; Bohari, Bohari (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The objective of this study was to analyze the role of cadres as an effort to increase knowledge and attitudes about chronic energy deficiency among adolescents in Mali-Mali village. METHODS: This type of research is quasi experimental. Researchers trained five cadres who provide education to junior high school students. The sampling technique used a total sampling of 38 female students. The treatment duration was 4 months with the evaluation of knowledge, attitude, and upper arm circumference measurement each month. RESULTS: This study’s results were that 21.1% of respondents had good knowledge about chronic energy deficiency before treatment. The evaluation of respondents who had good knowledge about chronic energy deficiency at 1st month was 57.9%. The 2nd month was 2 94.7%, the 3rd month was 100%, and the 4th month was 100%. Wilcoxon test showed a significant difference in knowledge at months 1, 2, and 3 with p < 0.05. There was no significant difference at month 4 with a result of p > 0.05. The evaluation results of respondents who had a good attitude about chronic energy deficiency before treatment were 26.3%. In comparison, after treatment was 42.1% in the 1st month, 57.9% in the 2nd month, 57.9% in the 3rd month, and 78.9% in the 4th month. The Chi-square test results showed no differences in attitudes at month 1, 2, and 3, while at month 4 found a significant relationship. The upper arm circumference measurement showed that the number of respondents who suffer from chronic energy deficiency was 25 people for 4 months. CONCLUSION: Cadres could improve knowledge and attitudes about chronic energy deficiency in female adolescents in Mali-Mali Village.